Analisis Tingkat Kesehatan Bank Umum Syariah Dan Bank Umum Konvensional Di Indonesia Berdasarkan Risk Profile, Good Corporate Governance, Earning And Capital (RGEC) - Ma'rifatul Hikmah; IGN Oka Widana (Institut Teknologi dan Bisnis Ahmad Dahlan Jakarta, 2021)
This study aims to compare health levels of Islamic Commercial Banks and Conventional Commercial Banks in Indonesia using descriptive methods. This study uses a measure of Risk Profile, Good Corporate Governance, Earning And Capital (RGEC), where the Risk Profile is measured using the NPL / NPF and LDR ratios, Good Corporate Governance uses the self-assessment results reported in the FSA, Earning uses the ROA ratio and Capital Using the CAR ratio. The comparison results show differences in the soundness of the Sharia Commercial Banks with Conventional Commercial Banks, which generally indicate that the soundness of Sharia Commercial Banks is healthier.